2012
DOI: 10.1111/j.1748-7692.2012.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of abundance and habitat usage for common bottlenose dolphins between sites exposed to differential anthropogenic stressors within the estuaries of southern Georgia, U.S.A

Abstract: The health of common bottlenose dolphins (Tursiops truncatus) within southern Georgia estuaries is of particular concern due to high levels of anthropogenic contaminants in their tissues. Dolphins in this region have the highest polychlorinated biphenyl (PCB) concentrations recorded for any marine mammal and these concentrations correlate to distance from a Superfund point‐source in the Turtle/Brunswick River Estuary (TBRE). Currently, little is known about the population structure of dolphins in this region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…Balmer et al . () suggested that depending on the length of time spent within the study area, these defined groups may use the habitat differently. Differences in habitat use among resident and transient individuals are also likely to occur along the Adelaide metropolitan coast, as individuals use different areas within the study site and for different periods of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balmer et al . () suggested that depending on the length of time spent within the study area, these defined groups may use the habitat differently. Differences in habitat use among resident and transient individuals are also likely to occur along the Adelaide metropolitan coast, as individuals use different areas within the study site and for different periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…, Balmer et al . ). Such data provide the basis for management decisions in environmental impact assessments, species conservation assessments, protected area design, conservation and research investment, and management intervention.…”
mentioning
confidence: 97%
“…These activities are a potential source of both acute and chronic stress, in both offshore and inshore waters ( e.g ., Balmer et al . , Rossman et al . , Baş et al .…”
mentioning
confidence: 99%
“…However, photo‐identification surveys provide additional data that cannot be obtained through telemetry alone and can be conducted without health assessments, which are not possible for many studies. For example, photo‐identification surveys in the SGA began in 2004 and have generated long‐term data on seasonal abundance, habitat use, and identification of different stocks using the region (Balmer et al ., ). Comparisons of individuals sighted within the SGA with photo‐identification catalogues along the east coast of the USA would reduce limitations associated with extended ranging patterns outside of the study area, at a cost for additional analysis time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the geographic delineations of many of these stocks overlap and apportioning abundance or mortality for a specific stock in the face of overlapping stocks is particularly difficult. There have been several studies in the south‐eastern USA that have provided insight into the geographic boundaries for common bottlenose dolphin stocks (Wells, ; Wells and Scott, ; Zolman, ; Balmer et al ., , ; Speakman et al ., ; Tyson et al ., ). These studies have often required multi‐year, capture–recapture, photo‐identification surveys and tissue sampling for genetic analysis to identify stock boundaries and estimate abundance.…”
Section: Introductionmentioning
confidence: 99%